Răspunsuri

2014-10-21T22:10:00+03:00
A) 2x+5=17
2x=17-5
2x=12
x=12:2
x=6
b) 3x-1=14
3x=14+1
3x=15
x=15:3
x=5
c) 2(5x-3)=94
5x-3=94:2
5x-3=47
5x=47+3
5x=50
x=50:5
x=10
d) 3(2x+7)-5=22
6x+21=22+5
6x+21=27
6x=27-21
6x=6
x=6:6
x=1

e) 5[2(3x+2)-11]+4=29
5(6x+4-11)=29-4
5(6x+4-11)=25
6x+4-11=25:5
6x+4-11=5
6x+4=5+11
6x+4=16
6x=16-4
6x=12
x=12:6
x=2
20 4 20
2014-10-21T22:12:26+03:00

a) 2x+5=17              b) 3x-1=14               c) 2(5x-3)=94

2x=12                          3x=15                       5x-3=94:2

x=12:2=6                     x=5                            5x-3=47

x=6                                                                 5x=50     x=10 

4 3 4